Prompt Photon Production at the Tevatron and LHC - Kumar Ashish (EPJ Web of Conferences, 2013)
Prompt photon production has been studied by the CDF and DØ experiments at the Fermilab Tevatron collider in pp̅ collisions at the centre of mass energy of √s = 1.96 TeV and by the ATLAS experiment at LHC in pp collisions at √s = 7 TeV.Measurements of the inclusive photon, inclusive photon plus jet, photon plus heavy flavor jet, and diphoton production cross sections are discussed. The results are compared to the perturbative QCD calculations and predictions from Monte Carlo generators.